Silicon Carbide and Magnetorresistive Technologies for Solid State Power Controllers - Garrigós A.; Blanes J. M.; Gutiérrez R.; Borrell J.; Maset E.; Ramirez D.; Cardoso S. (E3S Web of Conferences, 2017)
The aim of this paper is to make an introduction, review and preliminary investigation tasks of the application of Silicon Carbide (SiC) power semiconductors and magnetoresistive (MR) current sensors for Solid State Power Controllers (SSPCs) and controlled switches, especially for high temperature environment and/or high voltage applications.